Quick-setting and quick-hardening cement clinker as well as preparation method and application thereof
By optimizing the mineral composition of cement clinker, increasing the content of calcium sulfosilicate and controlling its mass ratio to dicalcium silicate, the problem of inhibition of Bailite when calcium sulfosilicate is higher than Bailite. The high early strength of cement clinker and stable growth in later strength have been achieved, reducing production energy consumption and carbon emissions.
Patent Information
- Application Number
- CN202411688678.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In cement clinker, when calcium sulfosilicate and Bellet exist at the same time and the calcium sulfosilicate content is higher than that of Bellet, the hydration of Bellet is inhibited, affecting the later strength development of cement clinker.
By optimizing the mineral composition, the content of calcium sulfosilicate is increased, while controlling the mass ratio of calcium sulfosilicate to dicalcium silicate, ensuring that the presence of calcium sulfosilicate does not inhibit the hydration of Bellet, forming a high early strength and Cement clinker with stable growth in strength in the later stage.
The early strength of cement clinker is achieved, the low firing temperature and stable growth in later strength is reduced, production energy consumption and carbon emissions are significantly improved, and the low-carbon advantages of cement are significantly improved.
Smart Images

Figure CN119430702A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a fast-setting and fast-hardening cement clinker and a preparation method and application thereof. Background Art
[0002] In ordinary Portland cement clinker, the main mineral is alite (C3S), whose calcium oxide content reaches 73.7% and the formation temperature is about 1450℃, resulting in a large amount of energy consumption and high levels of carbon emissions. Belite (C2S) can be quickly formed above 1250℃ and has a low calcium oxide content. Therefore, high belite cement has obvious advantages in low energy consumption and low carbon emissions. However, high belite cement is a low-heat Portland cement with belite as the dominant mineral. It has a slow hydration rate and low early strength, which limits its application and development. Sulphoaluminate cement has the characteristics of high early strength and low firing temperature due to the presence of a large amount of anhydrous calcium sulfoaluminate minerals (C4A3S), but the later strength growth is not significant. Therefore, combining the advantages of belite cement and sulphoaluminate cement, the development of high belite sulphoaluminate cement with belite and anhydrous calcium sulphoaluminate as the dominant minerals has become one of the research hotspots. Studies in recent years have shown that calcium sulfosilicate (C5S2S) can show stronger hydration activity than β-C2S in the sulfoaluminate system, and the formation temperature (900-1200℃) is lower than that of β-C2S. Therefore, the main mineral components of Belite sulfoaluminate cement are adjusted from dicalcium silicate and calcium sulfoaluminate to calcium sulfosilicate, dicalcium silicate and calcium sulfoaluminate to form dicalcium silicate-calcium sulfoaluminate-calcium sulfosilicate clinker. The elements of C5S2S mineral are richer than β-C2S but the calcium content is low, so dicalcium silicate-calcium sulfoaluminate-calcium sulfosilicate clinker can reduce the amount of limestone, improve the utilization rate of solid waste raw materials, effectively reduce the cement burning temperature, and reduce coal energy consumption. Therefore, the dicalcium silicate-calcium sulfosilicate-calcium sulfoaluminate cement system has a wide range of applications. However, when calcium sulfosilicate and belite exist simultaneously in the cement clinker and the content of calcium sulfosilicate is higher than that of belite, the dissolution of calcium sulfosilicate during the hydration process causes the silicon ions in the pore solution to reach saturation, resulting in the inhibition of belite hydration, thereby affecting the later strength development of the cement clinker.
[0003] However, when calcium sulfosilicate and belite exist simultaneously in cement clinker and the content of calcium sulfosilicate is higher than that of belite, the dissolution of calcium sulfosilicate during the hydration process causes the silicon ions in the pore solution to reach saturation, resulting in the inhibition of belite hydration, thus affecting the later strength development of cement clinker. Summary of the invention
[0004] The purpose of the present invention is to provide a fast-setting and fast-hardening cement clinker and a preparation method and application thereof, and to optimize the mineral composition of the clinker so as to make a dicalcium silicate-calcium sulfoaluminate-calcium sulfosilicate cement clinker having high early strength, low firing temperature and stable growth of late strength. To achieve the above purpose, the technical scheme adopted by the present invention is as follows:
[0005] A fast-setting and fast-hardening cement clinker, comprising the following mineral components in terms of mass fraction: 11.15-22.76wt% of calcium sulfosilicate, 22.21-28.00wt% of calcium sulfoaluminate, 39.28-45.72wt% of dicalcium silicate, 7.93-9.29wt% of calcium sulfate, 2.33-3.64wt% of iron phase, 0.49-1.52wt% of free calcium, and the remainder being mixed mineral components;
[0006] The clinker is composed of the following raw materials in terms of mass fraction: 51.0-52.0 wt % of limestone, 28.0-30.0 wt % of phosphogypsum, 9.0-11.0 wt % of fly ash, and 8.0-11.0 wt % of bauxite.
[0007] Furthermore, a fast-setting and fast-hardening cement clinker comprises the following mineral components by mass fraction: 15-20wt% calcium sulfosilicate, 23-25wt% calcium sulfoaluminate, 40-42wt% dicalcium silicate, 8-9wt% calcium sulfate, 2.5-3.2wt% iron phase, 0.5-1.2wt% free calcium, and the remainder is mixed mineral components;
[0008] The clinker is composed of the following raw materials in terms of mass fraction: 51.0-52.0 wt % of limestone, 28.0-29.0 wt % of phosphogypsum, 9.0-10.0 wt % of fly ash, and 8.0-10.0 wt % of bauxite.
[0009] Furthermore, the mass ratio of the dicalcium silicate to the calcium sulfosilicate is 1.73-3.95:1; the mass ratio of the calcium sulfosilicate to the calcium sulfoaluminate is 0.4-1.02:1; and the iron phase is calcium aluminoferrate.
[0010] Furthermore, the content of SO3 in the phosphogypsum is 40-45wt%.
[0011] Furthermore, the content of CaO in the limestone is 50-55wt%.
[0012] Furthermore, the content of SiO2 in the fly ash is 50-60wt%, and the content of A12O3 is 20-30wt%.
[0013] A method for preparing fast-setting and fast-hardening cement clinker comprises the following steps:
[0014] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0015] Step 2: Mix and grind the raw material powders obtained in step 1 according to their mass fractions to obtain cement raw material;
[0016] Step 3, adding water to the cement raw material, mixing and pressing into a corrugated test cake, and drying in an oven; preferably, the mass of water added is 10-12wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0017] Step 4: placing the dried corrugated test cake in a high-temperature furnace for calcination, and after calcination, quickly taking out the corrugated test cake and cooling it to room temperature to obtain the cement clinker; preferably, cooling is performed by fan rapid cooling.
[0018] Furthermore, the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%.
[0019] Furthermore, in step 4, the temperature is increased to 900°C at a heating rate of 10-20°C / min, the corrugated test cake is kept at 900°C for 20 minutes, and then the temperature is increased to 1210-1250°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1210-1250°C for 30-60 minutes.
[0020] The invention discloses an application of the fast-setting and fast-hardening cement clinker in preparing cement.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses calcium sulfosilicate to replace a small part of dicalcium silicate (belite). The presence of calcium sulfosilicate is beneficial to the development of cement clinker strength in the later stage; a small amount of calcium sulfosilicate ensures the full play of the hydration activity of belite, avoids the dissolution of a large amount of calcium sulfosilicate during the hydration process, makes the silicon ions in the pore solution reach saturation and inhibits the hydration of belite, and ensures the development of cement clinker strength in the later stage. In addition, there is also highly active α-C2S (α-dicalcium silicate) in the calcined cement clinker, and its hydration activity is higher than β-C2S (β-dicalcium silicate), which can provide guarantee for the development of cement clinker strength in the later stage together with calcium sulfosilicate.
[0023] 2. The calcination temperature of the cement clinker of the present invention is 1210-1250°C, which is about 200-250°C lower than the process temperature of ordinary Portland cement (OPC) and about 50-150°C lower than the process temperature of sulphoaluminate cement (CSA). It can effectively reduce production energy consumption, and the CO2 emission during the clinker preparation process is low, with significant low-carbon advantages.
[0024] 3. The cement clinker of the present invention contains a small amount of free calcium (f-CaO), which promotes the hydration of anhydrous calcium sulfoaluminate in the early stage of cement hydration, accelerating the early setting and hardening. Although the f-CaO of the present invention exceeds the maximum limit of 0.2wt% of f-CaO in ordinary sulfoaluminate cement clinker, the calcium sulfoaluminate content of the cement clinker of the present invention is only 22.21-28.00wt%, which is much lower than the content of 60-70wt% of anhydrous calcium sulfoaluminate minerals in ordinary sulfoaluminate cement clinker.
[0025] 4. The cement clinker of the present invention contains a certain amount of calcium sulfate (CaSO4), which reacts with calcium sulfoaluminate to form ettringite, which can promote the early strength development of the cement clinker. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD pattern of the cement clinker prepared in Example 1.
[0027] Figure 2 This is the XRD spectrum of the cement clinker prepared in Example 2.
[0028] Figure 3 This is the XRD spectrum of the cement clinker prepared in Example 3.
[0029] Figure 4 This is the XRD spectrum of the cement clinker prepared in Example 4.
[0030] Figure 5 This is the XRD spectrum of the cement clinker prepared in Example 5.
[0031] Figure 6 This is the XRD spectrum of the cement clinker prepared in Comparative Example 1.
[0032] Figure 7 This is the XRD pattern of the cement clinker of Comparative Example 2. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] As a preferred embodiment of the present invention, a fast-setting and fast-hardening cement clinker disclosed in this embodiment is composed of the following raw materials in mass fraction: 52.0wt% limestone, 28.0wt% phosphogypsum, 10.0wt% fly ash, and 10.0wt% bauxite.
[0036] A method for preparing a fast-setting and fast-hardening cement clinker in this embodiment comprises the following steps:
[0037] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0038] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0039] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0040] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and after the calcination is completed, the corrugated test cake is quickly taken out, and the fan is rapidly cooled to room temperature to obtain the cement clinker. The calcination is carried out by heating the temperature to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1230°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1230°C for 40min.
[0041] According to the Rietveld quantitative analysis, the mineral composition of the cement clinker of this embodiment is: 12.33wt% calcium sulfosilicate, 25.25wt% calcium sulfoaluminate, 45.72wt% dicalcium silicate, 8.01wt% calcium sulfate, 3.34wt% calcium aluminoferrite, 0.97wt% free calcium, and the remainder is mixed mineral components.
[0042] In this embodiment, 10 wt% of anhydrite is added to the cement clinker, and then the mixture is ground to a specific surface area of 447 m 2 / kg, made into cement.
[0043] Example 2
[0044] As a preferred embodiment of the present invention, a fast-setting and fast-hardening cement clinker disclosed in this embodiment is composed of the following raw materials in mass fraction: 51.5wt% limestone, 29.0wt% phosphogypsum, 10.5wt% fly ash, and 9.0wt% bauxite.
[0045] A method for preparing a fast-setting and fast-hardening cement clinker in this embodiment comprises the following steps:
[0046] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0047] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0048] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0049] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and after the calcination is completed, the corrugated test cake is quickly taken out, and the fan is rapidly cooled to room temperature to obtain the cement clinker. The calcination is carried out by heating the temperature to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1210°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1210°C for 60min.
[0050] According to the Rietveld quantitative analysis, the mineral composition of the cement clinker of this embodiment is: 15.90wt% calcium sulfosilicate, 23.96wt% calcium sulfoaluminate, 43.53wt% dicalcium silicate, 8.15wt% calcium sulfate, 3.64wt% calcium aluminoferrite, 0.84wt% free calcium, and the remainder is mixed mineral components.
[0051] In this embodiment, the cement clinker is mixed with 10 wt% of anhydrite by weight of the cement clinker, and then mixed and ground to a specific surface area of 452 m 2 / kg, made into cement.
[0052] Example 3
[0053] As a preferred embodiment of the present invention, a fast-setting and fast-hardening cement clinker disclosed in this embodiment is composed of the following raw materials in mass fraction: 52.0wt% limestone, 28.0wt% phosphogypsum, 9.0wt% fly ash, and 11.0wt% bauxite.
[0054] A method for preparing a fast-setting and fast-hardening cement clinker in this embodiment comprises the following steps:
[0055] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0056] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0057] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0058] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and after the calcination is completed, the corrugated test cake is quickly taken out, and the fan is rapidly cooled to room temperature to obtain the cement clinker. The calcination is carried out by heating the temperature to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1250°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1250°C for 40min.
[0059] According to the Rietveld quantitative analysis, the mineral composition of the cement clinker of this embodiment is: 12.13wt% calcium sulfosilicate, 28.00wt% calcium sulfoaluminate, 44.02wt% dicalcium silicate, 9.29wt% calcium sulfate, 2.33wt% calcium aluminoferrite, 0.49wt% free calcium, and the remainder is mixed mineral components.
[0060] In this embodiment, the cement clinker is mixed with 5 wt% of anhydrite by weight of the cement clinker, and then mixed and ground to a specific surface area of 443 m 2 / kg, made into cement.
[0061] Example 4
[0062] As a preferred embodiment of the present invention, a fast-setting and fast-hardening cement clinker disclosed in this embodiment is composed of the following raw materials in mass fraction: 52.0wt% limestone, 28.0wt% phosphogypsum, 9.0wt% fly ash, and 11.0wt% bauxite.
[0063] A method for preparing a fast-setting and fast-hardening cement clinker in this embodiment comprises the following steps:
[0064] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0065] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0066] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0067] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and after the calcination is completed, the corrugated test cake is quickly taken out, and the fan is rapidly cooled to room temperature to obtain the cement clinker. The calcination is carried out by heating the temperature to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1230°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1230°C for 40min.
[0068] According to the Rietveld quantitative analysis, the mineral composition of the cement clinker of this embodiment is: 11.15wt% calcium sulfosilicate, 27.93wt% calcium sulfoaluminate, 44.02wt% dicalcium silicate, 8.12wt% calcium sulfate, 2.99wt% calcium aluminoferrite, 1.52wt% free calcium, and the remainder is mixed mineral components.
[0069] In this embodiment, the cement clinker is mixed with 10 wt% of anhydrite by weight of the cement clinker, and then mixed and ground to a specific surface area of 449 m 2 / kg, made into cement.
[0070] Example 5
[0071] As a preferred embodiment of the present invention, a fast-setting and fast-hardening cement clinker disclosed in this embodiment is composed of the following raw materials in mass fraction: 51.0wt% limestone, 30.0wt% phosphogypsum, 11.0wt% fly ash, and 8.0wt% bauxite.
[0072] A method for preparing a fast-setting and fast-hardening cement clinker in this embodiment comprises the following steps:
[0073] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0074] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0075] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0076] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and after the calcination is completed, the corrugated test cake is quickly taken out, and the fan is rapidly cooled to room temperature to obtain the cement clinker. The calcination is carried out by heating the temperature to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1220°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1220°C for 40min.
[0077] According to the Rietveld quantitative analysis, the mineral composition of the cement clinker of this embodiment is: 22.76wt% calcium sulfosilicate, 22.21wt% calcium sulfoaluminate, 39.28wt% dicalcium silicate, 7.93wt% calcium sulfate, 3.13wt% calcium aluminoferrite, 1.16wt% free calcium, and the remainder is mixed mineral components.
[0078] The cement clinker of the embodiment is mixed with 10wt% of anhydrite of the cement clinker mass, and then mixed and ground to a specific surface area of 459m 2 / kg, made into cement.
[0079] Comparative Example 1
[0080] The cement clinker of this comparative example is composed of the following raw materials in terms of mass fraction: 49.0wt% of limestone, 21.0wt% of phosphogypsum, 9.0wt% of fly ash, and 21.0wt% of bauxite.
[0081] The preparation method of cement clinker in this comparative example comprises the following steps:
[0082] Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use;
[0083] Step 2, mixing and grinding the raw material powders obtained in step 1 according to the above mass ratio to obtain cement raw material, wherein the fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%;
[0084] Step 3, adding water to the cement raw material and mixing well, pressing into a corrugated test cake, and drying in an oven, the mass of water added is 10wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C;
[0085] Step 4, placing the dried corrugated test cake in a high-temperature furnace for calcining, and taking out the corrugated test cake quickly after calcination, and cooling it to room temperature by fan to obtain cement clinker, and calcining is heating to 900°C at a heating rate of 10-20°C / min, and the corrugated test cake is kept at 900°C for 20min, and then heated to 1200°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1200°C for 60min.
[0086] According to Rietveld quantitative analysis, the mineral composition of the cement clinker of this comparative example is: 28.56wt% calcium sulfosilicate, 41.94wt% calcium sulfoaluminate, 18.75wt% dicalcium silicate, 1.66wt% calcium sulfate, 3.16wt% calcium aluminoferrite, 0.01wt% free calcium, and the remainder is mixed mineral components.
[0087] The cement clinker of this comparative example was mixed with 10wt% of anhydrite, and then mixed and ground to a specific surface area of 437m 2 / kg, made into cement.
[0088] Comparative Example 2
[0089] This comparative example is a high-belite sulphoaluminate cement clinker produced by a certain unit, and the sintering temperature range of the clinker is 1350±25°C. According to Rietveld quantitative analysis, the mineral composition of the cement clinker is: tricalcium aluminate (shown as C3Amonoclinic) 3.06wt%, calcium sulphoaluminate 41.73wt%, dicalcium silicate 41.92wt%, calcium sulfate 2.53wt%, free calcium 0.12wt%, and the remainder is mixed mineral components.
[0090] In this comparative example, 15 wt% of anhydrite is added to the cement clinker, and then the mixture is ground to a specific surface area of 352 m 2 / kg, made into cement.
[0091] The mechanical properties of the cements of Examples 1 to 5 and Comparative Examples 1 to 5 were tested according to "Sulphoaluminate Cement" GB 20472-2006. The water consumption was determined based on a water-cement ratio of 0.47 (211.5 mL) and a mortar fluidity of 165 mm to 175 mm. The mechanical properties are shown in Table 1.
[0092] Table 1 Mechanical properties test results of various cements
[0093]
[0094] According to the data in Table 1, the 28d flexural strength of the cement prepared in the embodiment of the present invention meets the 28d flexural strength in the national general cement standard GB175-2007; the 28d compressive strength of the cement prepared in the embodiment of the present invention also meets the 28d compressive strength in the national general cement standard GB175-2007, and the 28d compressive strength of the cement in Example 1, Example 2 and Example 3 is much greater than the 28d compressive strength of the cement in Comparative Example 2. The content of calcium sulfosilicate in the mineral composition of the cement clinker in Comparative Example 1 is much higher than that of dicalcium silicate, resulting in the inhibition of belite hydration, thereby affecting the later strength development of the cement clinker, so the 28-day compressive strength of the cement in Comparative Example 1 is lower than the 28-day compressive strength of each example.
[0095] Figure 1 to Figure 5 The XRD patterns of the cement clinkers prepared in Examples 1 to 5 are respectively: Figure 6-7The XRD spectra of cement clinker of comparative example 1 and comparative example 2 are shown respectively. The XRD spectra of cement clinker prepared by changing the batching scheme and calcination temperature in Examples 1 to 5 show that the mineral composition range is: calcium sulfosilicate (Temesite in the figure) 11.15-22.76wt%, calcium sulfoaluminate (Ca4Al6O 12 SO4) 22.21 ~ 28.00wt%, dicalcium silicate (illustrated as all marks including C2S) 39.28 ~ 45.72wt%, calcium sulfate (illustrated as Anhydrite) 7.93 ~ 9.29wt%, calcium aluminoferrite (illustrated as C4AF Colville) 2.33 ~ 3.64wt%, free calcium (illustrated as Lime) 0.49 ~ 1.52wt%, and the calcium sulfosilicate content of the cement clinker is lower than the dicalcium silicate content, and contains a certain amount of calcium sulfate and free calcium. The XRD spectrum of the cement clinker of Comparative Example 1 shows that the types of mineral composition are the same as those of Examples 1 to 5, but the calcium sulfosilicate content (28.56wt%) of the cement clinker is higher than the dicalcium silicate content (18.75wt%), and the calcium sulfate and free calcium contents are low. The XRD spectrum of the cement clinker of Comparative Example 2 shows that the main minerals are calcium sulfoaluminate and dicalcium silicate, and the calcium sulfate and free calcium contents are low.
[0096] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields is also included in the patent protection scope of the present invention.
Claims
1. A fast-setting and fast-hardening cement clinker, characterized in that: The invention comprises the following mineral components in terms of mass fraction: 11.15-22.76wt% calcium sulfosilicate, 22.21-28.00wt% calcium sulfoaluminate, 39.28-45.72wt% dicalcium silicate, 7.93-9.29wt% calcium sulfate, 2.33-3.64wt% iron phase, 0.49-1.52wt% free calcium, and the remainder is mixed mineral components; The clinker is composed of the following raw materials in terms of mass fraction: 51.0-52.0 wt % of limestone, 28.0-30.0 wt % of phosphogypsum, 9.0-11.0 wt % of fly ash, and 8.0-11.0 wt % of bauxite.
2. The fast-setting and fast-hardening cement clinker according to claim 1, characterized in that: The invention comprises the following mineral components by mass fraction: 15-20wt% calcium sulfosilicate, 23-25wt% calcium sulfoaluminate, 40-42wt% dicalcium silicate, 8-9wt% calcium sulfate, 2.5-3.2wt% iron phase, 0.5-1.2wt% free calcium, and the remainder is mixed mineral components; The clinker is composed of the following raw materials in terms of mass fraction: 51.0-52.0 wt % of limestone, 28.0-29.0 wt % of phosphogypsum, 9.0-10.0 wt % of fly ash, and 8.0-10.0 wt % of bauxite.
3. The fast-setting and fast-hardening cement clinker according to claim 1, characterized in that: The mass ratio of the dicalcium silicate to the calcium sulfosilicate is 1.73-3.95:1; the mass ratio of the calcium sulfosilicate to the calcium sulfoaluminate is 0.4-1.02:1; and the iron phase is calcium aluminoferrate.
4. The fast-setting and fast-hardening cement clinker according to claim 1, characterized in that: The content of SO3 in the phosphogypsum is 40-45wt%.
5. The fast-setting and fast-hardening cement clinker according to claim 1, characterized in that: The content of CaO in the limestone is 50-55wt%.
6. The fast-setting and fast-hardening cement clinker according to claim 1, characterized in that: The content of SiO2 in the fly ash is 50-60wt%, and the content of A12O3 is 20-30wt%.
7. The method for preparing fast-setting and fast-hardening cement clinker according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, drying the raw materials limestone, phosphogypsum, fly ash and bauxite, crushing and grinding them into corresponding raw material powders for standby use; Step 2: Mix and grind the raw material powders obtained in step 1 according to their mass fractions to obtain cement raw material; Step 3, adding water to the cement raw material, mixing and pressing into a corrugated test cake, and drying in an oven; preferably, the mass of water added is 10-12wt% of the mass of the cement raw material, the size of the corrugated test cake is 13mm×10mm, and the oven temperature is 105°C; Step 4: placing the dried corrugated test cake in a high-temperature furnace for calcination, and after calcination, quickly taking out the corrugated test cake and cooling it to room temperature to obtain the cement clinker; preferably, cooling is performed by fan rapid cooling.
8. The method for preparing a fast-setting and fast-hardening cement clinker according to claim 7, characterized in that: The fineness of the cement raw material satisfies that the residue on an 80 μm sieve is less than 12%.
9. The method for preparing a fast-setting and fast-hardening cement clinker according to claim 7, characterized in that: In step 4, the temperature is increased to 900°C at a heating rate of 10-20°C / min, the corrugated test cake is kept at 900°C for 20 minutes, and then the temperature is increased to 1210-1250°C at a heating rate of 5-10°C / min, and the corrugated test cake is kept at 1210-1250°C for 30-60 minutes.
10. Use of the fast-setting and fast-hardening cement clinker according to any one of claims 1 to 6 in preparing cement.
Citation Information
Patent Citations
High belite-calcium sulphoaluminate-calcium sulphosilicate cement clinker and preparation method thereof
CN114213043A
Dicalcium silicate-calcium sulphoaluminate-calcium sulphosilicate raw material, clinker and cement preparation method
CN116621478A